Bionic super-hydrophobic degerming film for surface of household paving material and preparation method of bionic super-hydrophobic degerming film

By designing a bionic superhydrophobic sterilization film on the surface of home decoration materials, combining the ratio of specific nanomaterials and resins, the problem of limited effects of existing superhydrophobic surfaces in preventing microbial adhesion and proliferation is solved, and the membrane is realized Superhydrophobic, antibacterial and self-cleaning properties.

CN119463659APending Publication Date: 2025-02-18NANJING MGM NEW MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411453011.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing superhydrophobic surfaces have limited effectiveness in preventing microbial adhesion and proliferation, and in some cases can promote microbial adhesion.

Method used

Design a bionic superhydrophobic sterilization film for the surface of home decoration materials. By laying the film on a superhydrophobic modified layer with a concave micro-nanostructure, it combines acetastic nanofibers and silica nanoparticles, The specific ratio of silane-polyurethane resin, tannin acid and titanium dioxide nanoparticles forms a film with superhydrophobic, antibacterial and self-cleaning properties.

Benefits of technology

It realizes superhydrophobicity and antibacterial properties of the membrane surface, which can effectively inhibit the adhesion and proliferation of E. coli and Staphylococcus aureus, and keep the indoor environment clean and healthy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463659A_ABST
    Figure CN119463659A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a coating film capable of ensuring the super-hydrophobicity of a product and meeting the cleaning performance of the product. Therefore, the invention provides the bionic super-hydrophobic degerming film for the surface of the household paving material, and the bionic super-hydrophobic degerming film is applied to the super-hydrophobic modified layer with the concave micro-nano structure; the method is specially used in cooperation with a bionic super-hydrophobic layer. The membrane is prepared from palygorskite nanofibers, silicon dioxide nanoparticles, silane-polyurethane resin, tannic acid and titanium dioxide nanoparticles. Compared with the prior art, the bionic super-hydrophobic degerming film for the surface of the household paving material and the preparation method thereof have the advantages that the mass ratio of the solid component to the liquid component is kept balanced, so that mixing and coating are facilitated. Meanwhile, the proportion gives consideration to multiple functions such as mechanical property, chemical stability, antibacterial property and photocatalytic activity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a bionic super-hydrophobic sterilization film for the surface of household paving materials and a preparation method thereof. Background Art

[0002] In the past decade, bionic superhydrophobic surfaces have experienced rapid development as materials for resisting microbial adhesion. The reason behind this development is that superhydrophobic surfaces can form a trapped air layer when immersed, which is considered to be a key factor in effectively inhibiting biological contamination. Regarding the anti-adhesion mechanism of the air layer, one of the widely accepted ones is the barrier effect. When the superhydrophobic surface comes into contact with a liquid, the air layer is sandwiched between the liquid and the surface, forming a solid air-liquid interface. Due to the high tension of this interface, microorganisms cannot cross this interface and thus have difficulty adhering to the surface. Therefore, the air layer acts as a barrier between the surface and the liquid environment, effectively preventing microorganisms from finding effective sites for adhesion.

[0003] In addition, the trapped air layer underwater also inhibits the adhesion of microorganisms by interfering with their surface sensing. Normally, free-swimming microorganisms are able to show recognition ability when approaching a surface. However, due to the presence of the air layer, the superhydrophobic surface is camouflaged, making it impossible for microorganisms to sense the existence of the surface. Therefore, microorganisms cannot exert the necessary adhesion force, and their adhesion on the superhydrophobic surface with an air layer is greatly inhibited.

[0004] The invention patent "A kind of durable superhydrophobic self-cleaning and anti-slip ceramic tile and its preparation method" with patent number 202211636614.X in the prior art discloses a kind of durable superhydrophobic self-cleaning and anti-slip ceramic tile, including a green body with a glaze and an ink pattern layer, and also including a concave micro-nano structure applied on the surface of the green body, and the concave micro-nano structure is attached with a superhydrophobic modified layer; the concave micro-nano structure is an anti-slip protective glaze layer formed by applying anti-slip protective powder on the surface of the green body, and the glaze surface of the anti-slip protective glaze layer is pressed using a mold with a convex four-rhombus pyramid structure; the concave micro-nano structure includes a concave four-rhombus pyramid structure and a bubble pore structure; the present application forms a concave micro-nano structure on the surface of the ceramic tile, and then performs low surface energy modification to obtain a ceramic tile with durable superhydrophobic self-cleaning and anti-slip functions.

[0005] However, although the document states that the patented product has a long-lasting superhydrophobic self-cleaning function, according to the latest research, some superhydrophobic surfaces have been proven to be unable to effectively prevent the adhesion and proliferation of microorganisms on the surface, and even promote adhesion in some cases. To this end, Professor Zhao Jie from the team of Academician Ren Luquan of Jilin University and Associate Professor Jiang Rujian of Shandong First Medical University published a review article entitled "Bioispin superhydrophobic surfaces, inhibiting or promoting microbial adhesion?" in the journal Materials Today (https: / / doi.org / 10.1016 / j.mattod.2023.06.006), systematically explaining and clarifying the relationship between superhydrophobicity and microbial adhesion and the mechanism of action of superhydrophobic surfaces against microbial adhesion. Starting from the three factors related to superhydrophobicity, namely the air layer trapped on the superhydrophobic surface, surface roughness and solid surface energy, this paper comprehensively reveals the indirect correlation between microbial adhesion and surface superhydrophobicity, and clarifies that surface roughness and micro-nano morphology and low surface energy of solids are not only factors in constructing superhydrophobic surfaces, but also have a direct impact on the adhesion of microorganisms on the surface.

[0006] This paper explains why biomimetic superhydrophobic surfaces may not be able to effectively inhibit microbial invasion. Based on the understanding of the air layer, surface morphology and substrate surface energy acting individually and synergistically, the conclusions summarized in this paper will provide guidance for the design and manufacture of superhydrophobic surfaces with enhanced anti-biofouling properties and their wide application in treating surface contamination caused by microorganisms. It can be seen that the self-cleaning superhydrophobic surfaces prepared in the prior art do not achieve the claimed effect. Summary of the invention

[0007] In view of the shortcomings of the prior art, the applicant designed a bionic super-hydrophobic sterilization membrane for the surface of home paving materials under the guidance of the above-mentioned paper concept. It is specially used in conjunction with the bionic super-hydrophobic layer to ensure the super-hydrophobicity of the product while also meeting its cleaning performance. It is especially effective in keeping the interior clean in modern homes.

[0008] In this regard, the present invention provides a bionic super-hydrophobic sterilization film for the surface of home paving materials, which is applied on a super-hydrophobic modified layer with a concave micro-nano structure; the film comprises the following raw materials in terms of mass percentage:

[0009] Palygorskite nanofiber: 5%-8%;

[0010] Silica nanoparticles: 10%-16%;

[0011] Silane-polyurethane resin: 30%-45%

[0012] Tannic acid: 25%-35%;

[0013] Titanium dioxide nanoparticles: 15%;

[0014] The preparation method comprises the following steps:

[0015] Taking half of the mass of tannic acid and adding it into water to fully dissolve it to form a solution, placing palygorskite nanofibers in the solution, adding silicon dioxide nanoparticles and stirring evenly, so that the silicon dioxide nanoparticles are in-situ grown on the surface of the palygorskite nanofibers to form a first composite solution;

[0016] adding silane-polyurethane resin to the first composite solution and stirring evenly, so that the silane-polyurethane resin is grafted to the first composite solution containing silica nanoparticles / palyogorite nanofibers to form a second composite solution;

[0017] The other half of the mass of tannic acid is dissolved in water, titanium dioxide nanoparticles are added and stirred evenly to form a third composite solution; the third composite solution is then added dropwise to the second composite solution, and stirring is performed during the adding process to obtain a finished composite solution.

[0018] Preferably, for conventional finished products, the ratio usually selected is:

[0019] The palygorskite nanofiber: 5%;

[0020] Silica nanoparticles: 10%;

[0021] Silane-polyurethane resin: 45%;

[0022] Tannic acid: 25%;

[0023] Titanium dioxide nanoparticles: 15%. This ratio can fully meet the sterilization needs of the home.

[0024] Preferably, for scenes with high requirements for self-cleaning effect, the commonly used ratio is:

[0025] The palygorskite nanofiber: 8%;

[0026] Silica nanoparticles: 16%;

[0027] Silane-polyurethane resin: 30%;

[0028] Tannic acid: 31%;

[0029] Titanium dioxide nanoparticles: 15%. This ratio is usually used in medical settings.

[0030] Preferably, the titanium dioxide nanoparticles have a particle size of 5 nanometers. Too large a particle size of titanium dioxide nanoparticles is not conducive to their reaction in the solution, but titanium dioxide nanoparticles with a particle size of less than 5 nanometers have poor dispersibility in the solution and are difficult to achieve true dissolution, but instead form a stable suspension. Therefore, the selection of titanium dioxide nanoparticles with a particle size of 5 nanometers is the optimal solution.

[0031] Preferably, the grafting process comprises the steps of:

[0032] S1. Select appropriate silane-polyurethane resin: the silane part should react with the hydroxyl groups on the surface of silica nanoparticles, and the polyurethane part should interact with the functional groups on the surface of palygorskite nanofibers;

[0033] S2. Surface treatment: In the tannic acid environment, more hydroxyl and carboxyl groups are exposed on the surface of palygorskite;

[0034] S3, silane-polyurethane resin and silica / palygorskite nanofibers were all modified to achieve click grafting; the grafting reaction was carried out at room temperature for 40 minutes and then the temperature was raised to 65 degrees Celsius for 60 minutes to obtain the best grafting efficiency and distribution uniformity.

[0035] Preferably, the type of silane in the silane-polyurethane resin is one of chlorosilane, methoxysilane and aminosilane.

[0036] Furthermore, the present invention can also carry out characterization and performance testing steps as needed, using infrared spectroscopy analysis to characterize the structure and grafting degree of the grafted product.

[0037] The mechanical strength and thermal stability of the final composite material were tested to evaluate the grafting modification effect.

[0038] Preferably, the coating process comprises the following steps:

[0039] S1: Pretreatment: The pretreatment step includes substrate cleaning: using ultrasonic cleaning to remove impurities such as pollutants, grease, oxides, etc. on the substrate surface; ensuring that the clean substrate surface is conducive to the attachment and growth of the film. Chemical etching cannot be used in the present invention because it will destroy the nano-hydrophobic structure on the substrate surface.

[0040] S2: Pre-baking: Baking the substrate to a certain temperature to remove moisture and adsorbed gases in preparation for deposition; the temperature of the substrate is adjusted according to its material; usually for ceramic substrates this temperature is around 200 degrees Celsius, while for wood it is 70-130 degrees Celsius;

[0041] S3: vacuum reaction chamber preparation: placing the treated substrate into the vacuum reaction chamber, and vapor deposition is performed in a low pressure or vacuum environment to ensure that the reaction gas molecules can move freely and reach the substrate surface;

[0042] S4: heating the vacuum reaction chamber to a corresponding temperature according to the difference in substrate material and the preparation process of the super-hydrophobic modified layer of the concave micro-nano structure.

[0043] S5: atomizing the prepared solution into fine droplets, and in the deposition chamber, using plasma, electron beam bombardment or laser irradiation to excite the atomized molecules into an active state to increase their adhesion and reactivity;

[0044] S6: Thin film growth: The atomized molecules undergo physical deposition, and the deposits adhere to the surface of the substrate to form a thin film. In this process, the thickness, crystal structure, density and other properties of the thin film are regulated by controlling parameters such as deposition time, atomized molecule flow rate, temperature, and pressure.

[0045] S7: After the process is completed, the atomized molecule delivery is stopped and the reaction chamber is slowly restored to normal pressure.

[0046] Preferably, in step S6, the ceramic substrate is dried at 300 degrees Celsius in a vacuum reaction chamber for 20-60 seconds and then cured at room temperature for 8 hours.

[0047] Preferably, the substrate is taken out and then annealed and cooled as a post-processing step to further improve the performance of the film.

[0048] Compared with the prior art, the present invention is used to prepare a sterilization membrane with a biomimetic super-hydrophobic layer, and the mass ratio of the components used is balanced between the solid component and the liquid component for mixing and coating. At the same time, this ratio takes into account the mechanical properties, chemical stability, antibacterial properties, photocatalytic activity and other functions of the material. Ultimately, the finished membrane is ensured to have the following properties:

[0049] Super hydrophobicity: The contact angle of the membrane surface is less than 150°, with good water resistance and self-cleaning properties.

[0050] Antibacterial property: The killing rates of Escherichia coli and Staphylococcus aureus on the membrane surface are both over 99%.

[0051] Stability: The membrane has good mechanical stability and corrosion resistance.

[0052] The promotion of such antibacterial films in home paving materials such as bathrooms and kitchens can keep the corresponding areas clean and relatively dry for a long time, which is conducive to maintaining a clean and healthy indoor environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention.

[0054] Figure 1 The present invention is a schematic diagram of the preparation process of a bionic superhydrophobic antibacterial film for the surface of home paving materials.

[0055] Figure 2 The present invention is a schematic diagram of the use process of a bionic super-hydrophobic antibacterial film for the surface of household paving materials. DETAILED DESCRIPTION

[0056] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It can be understood that the specific implementation methods described here are only used to explain the relevant content, rather than to limit the present disclosure.

[0057] The adhesion and reproduction of bacteria on the surface of carriers has always been a difficult problem for global public health. Bacterial surface adhesion is the initial stage of biofilm formation. Compared with planktonic bacteria, bacteria in biofilms are less sensitive to antimicrobial agents and are more adaptable to complex environments. This pollution poses a huge threat and economic burden in various occasions. For example, in the use of indoor homes, the decline in cleanliness will affect the user's physical health and usage status, and will also increase the frequency and cost of cleaning. In the process of household material processing, especially in places such as kitchens or bathrooms where there are often water stains or bacterial growth, the existing technology has actually been trying to develop antibacterial or anti-slip materials as much as possible. However, it was found in the research process that the existing technology is actually limited in effectiveness in preventing bacterial growth. Therefore, it is very practical to develop surface materials that have the ability to resist bacterial adhesion and proliferation. Strategies to inhibit or slow down biofilm formation mainly rely on resisting initial cell adhesion. Among these strategies, superhydrophobic surfaces inspired by lotus leaves have been widely proven to resist bacterial adhesion because there is a stable air layer between the liquid and the surface, minimizing direct contact between bacteria and the coating. However, due to the inherent mechanical and air layer stability of superhydrophobic surfaces, these surfaces are still limited in antibacterial applications. There is a threshold value for the antibacterial effect of super-hydrophobic surfaces, and a single local super-hydrophobic surface lacks a good active antibacterial effect. Although some super-hydrophobic surfaces will physically eliminate bacteria when they invade the coating, they do not have enough ability to harm some specific bacteria. Therefore, in order to solve the limitations of the antibacterial effect of the passive defense strategy of super-hydrophobic coatings, for the application environment of these antibacterial materials, the present invention provides a bionic super-hydrophobic sterilization film for the surface of home paving materials, which gives the coating an active antibacterial strategy.

[0058] It should be noted here that the home paving materials described in the present invention refer to various materials used for decoration and paving of indoor floors, walls, ceilings, etc. The selection of these materials has a crucial impact on the aesthetics, practicality, durability of the home and the comfort of the residents. Home paving materials are generally considered to include floor materials such as solid wood floors, laminate floors, tiles, carpets; wall materials such as wallpaper, tiles, wood veneers, as well as gypsum boards, glass and other metal materials. However, in the present invention, ceramic materials such as tiles and wood can actually be processed. Among them, experiments have been successful on ceramic surfaces, while wood only has theoretical support. There are still some problems in the processing process, and the finished product has not yet reached the ideal state.

[0059] The present invention proposes the following specific implementation methods: Example 1: For conventional finished products, the commonly used ratio is:

[0060] The palygorskite nanofiber: 5%;

[0061] Silica nanoparticles: 10%;

[0062] Silane-polyurethane resin: 45%;

[0063] Tannic acid: 25%;

[0064] Titanium dioxide nanoparticles: 15%. This ratio can fully meet the sterilization needs of the home. The preparation method includes the following steps:

[0065] Taking half of the mass of tannic acid and adding it into water to fully dissolve it to form a solution, placing palygorskite nanofibers in the solution, adding silicon dioxide nanoparticles and stirring evenly, so that the silicon dioxide nanoparticles are in-situ grown on the surface of the palygorskite nanofibers to form a first composite solution;

[0066] adding silane-polyurethane resin to the first composite solution and stirring evenly, so that the silane-polyurethane resin is grafted to the first composite solution containing silica nanoparticles / palyogorite nanofibers to form a second composite solution;

[0067] The other half of the mass of tannic acid is dissolved in water, titanium dioxide nanoparticles are added and stirred evenly to form a third composite solution; the third composite solution is then added dropwise to the second composite solution, and stirring is performed during the adding process to obtain a finished composite solution.

[0068] The titanium dioxide nanoparticles have a particle size of 5 nanometers. Too large a particle size of titanium dioxide nanoparticles is not conducive to their reaction in the solution, but titanium dioxide nanoparticles with a particle size of less than 5 nanometers have poor dispersibility in the solution and are difficult to achieve true dissolution, but instead form a stable suspension. Therefore, the titanium dioxide nanoparticles with a particle size of 5 nanometers are selected as the optimal solution.

[0069] The grafting process comprises the steps of:

[0070] S1. Select appropriate silane-polyurethane resin: the silane part should react with the hydroxyl groups on the surface of silica nanoparticles, and the polyurethane part should interact with the functional groups on the surface of palygorskite nanofibers;

[0071] S2. Surface treatment: In the tannic acid environment, more hydroxyl and carboxyl groups are exposed on the surface of palygorskite;

[0072] S3, silane-polyurethane resin and silica / palygorskite nanofibers were all modified to achieve click grafting; the grafting reaction was carried out at room temperature for 40 minutes and then the temperature was raised to 65 degrees Celsius for 60 minutes to obtain the best grafting efficiency and distribution uniformity.

[0073] The type of silane in the silane-polyurethane resin is one of chlorosilane, methoxysilane and aminosilane.

[0074] Furthermore, the present invention can also carry out characterization and performance testing steps as needed, using infrared spectroscopy (FT IR) analysis to characterize the structure and grafting degree of the grafted product.

[0075] The mechanical strength and thermal stability of the final composite material were tested to evaluate the grafting modification effect. Such a product can fully meet the requirements of self-cleaning and sterilization at home.

[0076] Example 2: For scenes with high requirements for self-cleaning effects, the commonly used ratio is:

[0077] The palygorskite nanofiber: 8%;

[0078] Silica nanoparticles: 16%;

[0079] Silane-polyurethane resin: 30%;

[0080] Tannic acid: 31%;

[0081] Titanium dioxide nanoparticles: 15%. Such a ratio is usually used in medical environments. The preparation method includes the following steps:

[0082] Taking half of the mass of tannic acid and adding it into water to fully dissolve it to form a solution, placing palygorskite nanofibers in the solution, adding silicon dioxide nanoparticles and stirring evenly, so that the silicon dioxide nanoparticles are in-situ grown on the surface of the palygorskite nanofibers to form a first composite solution;

[0083] adding silane-polyurethane resin to the first composite solution and stirring evenly, so that the silane-polyurethane resin is grafted to the first composite solution containing silica nanoparticles / palyogorite nanofibers to form a second composite solution;

[0084] The other half of the mass of tannic acid is dissolved in water, titanium dioxide nanoparticles are added and stirred evenly to form a third composite solution; the third composite solution is then added dropwise to the second composite solution, and stirring is performed during the adding process to obtain a finished composite solution.

[0085] The titanium dioxide nanoparticles have a particle size of 5 nanometers. Too large a particle size of titanium dioxide nanoparticles is not conducive to their reaction in the solution, but titanium dioxide nanoparticles with a particle size of less than 5 nanometers have poor dispersibility in the solution and are difficult to achieve true dissolution, but instead form a stable suspension. Therefore, the titanium dioxide nanoparticles with a particle size of 5 nanometers are selected as the optimal solution.

[0086] The grafting process comprises the steps of:

[0087] S1. Select appropriate silane-polyurethane resin: the silane part should react with the hydroxyl groups on the surface of silica nanoparticles, and the polyurethane part should interact with the functional groups on the surface of palygorskite nanofibers;

[0088] S2. Surface treatment: In the tannic acid environment, more hydroxyl and carboxyl groups are exposed on the surface of palygorskite;

[0089] S3, silane-polyurethane resin and silica / palygorskite nanofibers were all modified to achieve click grafting; the grafting reaction was carried out at room temperature for 40 minutes and then the temperature was raised to 65 degrees Celsius for 60 minutes to obtain the best grafting efficiency and distribution uniformity.

[0090] The type of silane in the silane-polyurethane resin is one of chlorosilane, methoxysilane and aminosilane.

[0091] Furthermore, the present invention can also carry out characterization and performance testing steps as needed, using infrared spectroscopy (FT IR) analysis to characterize the structure and grafting degree of the grafted product. The mechanical strength and thermal stability of the final composite material are tested to evaluate the grafting modification effect. Such a finished product can be used in hospitals, restaurants and other places with higher requirements for environmental hygiene.

[0092] The membrane raw materials prepared in the above different embodiments are different, but the membrane process is the same, including the following steps:

[0093] S1: Pretreatment: The pretreatment step includes substrate cleaning: using ultrasonic cleaning to remove impurities such as pollutants, grease, oxides, etc. on the substrate surface; ensuring that the clean substrate surface is conducive to the attachment and growth of the film. Chemical etching cannot be used in the present invention because it will destroy the nano-hydrophobic structure on the substrate surface.

[0094] S2: Pre-baking: Baking the substrate to a certain temperature to remove moisture and adsorbed gases in preparation for deposition; the temperature of the substrate is adjusted according to its material; usually for ceramic substrates this temperature is around 200 degrees Celsius, while for wood it is 70-130 degrees Celsius;

[0095] S3: vacuum reaction chamber preparation: placing the treated substrate into the vacuum reaction chamber, and vapor deposition is performed in a low pressure or vacuum environment to ensure that the reaction gas molecules can move freely and reach the substrate surface;

[0096] S4: heating the vacuum reaction chamber to a corresponding temperature according to the difference in substrate material and the preparation process of the super-hydrophobic modified layer of the concave micro-nano structure.

[0097] S5: atomizing the prepared solution into fine droplets, and in the deposition chamber, using plasma, electron beam bombardment or laser irradiation to excite the atomized molecules into an active state to increase their adhesion and reactivity;

[0098] S6: Thin film growth: The atomized molecules undergo physical deposition, and the deposits adhere to the surface of the substrate to form a thin film. In this process, the thickness, crystal structure, density and other properties of the thin film are regulated by controlling parameters such as deposition time, atomized molecule flow rate, temperature, and pressure.

[0099] S7: After the process is completed, the atomized molecule delivery is stopped and the reaction chamber is slowly restored to normal pressure.

[0100] In step S5, plasma, electron beam bombardment or laser irradiation processes are involved. In fact, these processes can be realized by purchasing related equipment. For example, the plasma process involves a plasma cleaning machine or a plasma surface treatment instrument. Its working principle is to set two electrodes in a sealed container to form an electric field, and use a vacuum pump to achieve a certain vacuum degree. As the gas becomes thinner and thinner, the molecular distance and the free movement distance of molecules or ions become longer and longer. Under the action of the electric field, they collide to form plasma. The activity of these ions is very high, and their energy is enough to destroy almost all chemical bonds, causing chemical reactions on any exposed surface, so as to achieve the purpose of cleaning and modification. The conventional plasma cleaning machines that can be used in the present invention on the market now need to have some special functions such as precise temperature and gas flow control, and require a large processing volume, such as an industrial plasma cleaning machine of 10-20L, which is moderately priced but inconvenient to use.

[0101] Electron beam bombardment requires a medium-sized electron beam welder, which is relatively expensive. However, due to the high cost of electron beam welders and the high temperature during processing, they are not particularly suitable for the scenarios corresponding to the present invention.

[0102] The laser irradiation process uses high-energy lasers to irradiate materials to change their physical properties. The laser irradiation process is highly controllable. The laser irradiator can accurately control the energy, power, time and other parameters of the laser through a computer control system. Moreover, the basic model can meet the scenarios required by the present invention, and the cost is not high. Therefore, the applicant mainly uses a laser irradiator to implement the technical solution of the present invention in actual operation.

[0103] In step S6, the ceramic substrate is dried in a vacuum reaction chamber at 300 degrees Celsius for 20-60 seconds and then cured at room temperature for 8 hours. The substrate is taken out and annealed and cooled as a post-processing step to further improve the performance of the membrane.

[0104] Through such an implementation method, a self-cleaning and sterilization membrane that meets household-level requirements can be prepared in combination with a bionic super-hydrophobic layer, which can keep the home environment clean for a longer period of time and reduce the cost incurred during the cleaning process.

[0105] The bionic super-hydrophobic layer after adopting the technical solution of the present invention is tested for surface pollution resistance according to the provisions of 4.41 of GB / T 17657-2013. The specific steps are as follows:

[0106] Prepare the test equipment including:

[0107] a) Dropper!

[0108] b) 40mm diameter surface inverted bearing:

[0109] e) Scraper.

[0110] Get liquid or paste contaminants

[0111] The test does not specify what pollutants to use for the pollution resistance test. Usually, it is based on the application scenario of the corresponding household materials. For example, fermented and moldy kitchen waste pollutants are used as an example of common pollutants in the kitchen.

[0112] Cleaning and decontamination materials include

[0113] a) Dry white cotton cloth:

[0114] b) water;

[0115] c) Neutral detergent or oil cleaner recommended by the floor manufacturer,

[0116] d) Decontamination powder.

[0117] lighting fixtures

[0118] The lamp with a color temperature of 5500K~6500K is installed above the observation platform and illuminates the test piece vertically, providing an illumination of (1500±100)1x. The surrounding environment should be kept dark during the test to avoid affecting the test observation results.

[0119] It is also necessary to prepare a rotating observation platform that can be rotated so that the test piece can be observed in all directions under the lighting conditions specified in the standard.

[0120] In the center of the test piece, use a clean dropper to drop a small amount of liquid pollutant for the test. Place the convex surface of the watch glass on the dripped liquid and remove the watch glass immediately. If the diameter of the diffused pollutant exceeds 15mm, place the watch glass on the liquid again until the diameter of the diffused pollutant is 20mm-22mm and then remove it. If the diameter of the diffused pollutant is less than 15mm, add some more pollutant and use the watch glass to diffuse the pollutant again until the diameter of the pollutant on the test piece is 20mm-22mm.

[0121] Use a scraper to apply about 1 mL of the test paste onto the surface of the test piece, with a coverage diameter of 20 mm to 22 mm and a coating thickness of 2.5 mm to 3.0 mm.

[0122] The contact time between the specimen and the pollutant is 2 hours, which is the standard requirement.

[0123] Use dry white cotton cloth to wipe off liquid contaminants, or use a scraper to scrape off paste contaminants and then wipe with dry white cotton cloth, removing stains from the edge to the center.

[0124] Install the specimen on the observation platform, observe the specimen at a distance of 0.8m from the specimen at a 45° angle under the lighting device specified in the standard, and slowly rotate the observation platform to observe the specimen in all directions. If all the pollutants disappear, the pollution resistance level of the specimen is evaluated as level 0.

[0125] The self-cleaning and sterilizing film treated by the present invention maintains a pollution resistance level of 0 under this test condition. At the same time, when the test piece is tried to contact the pollutant for 24 hours, the pollution resistance level can still be guaranteed to be 0.

[0126] After the specimen has been in contact with the pollutant for 48-120 hours, install the specimen on the observation platform. Under the lighting device specified in the standard, observe the specimen at a distance of 0.8m from the specimen at a 45° angle. Slowly rotate the observation platform to observe the specimen in all directions. If there may still be stains, continue to clean it with water. After rinsing, dry the water and observe again. At this time, it should be ensured that the stains are completely gone and the pollution resistance level is guaranteed to be Level 1.

[0127] The above are merely examples tested according to the standards. In fact, the antibacterial and anti-fouling performance of the present invention is much higher than this.

[0128] Although the present invention is disclosed as above with preferred embodiments, it is not intended to limit the scope of the present invention. Any person of ordinary skill in the art can make some improvements without departing from the scope of the present invention, that is, all equivalent improvements made in accordance with the present invention should be covered by the scope of the present invention. In the description of this specification, the description of reference terms "an embodiment / method", "some embodiments / methods", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments / methods or examples in a suitable manner. In addition, without contradicting each other, a person of ordinary skill in the art can combine and combine the different embodiments / methods or examples described in this specification and the features of different embodiments / methods or examples.

[0129] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0130] Those skilled in the art should understand that the above embodiments are only for the purpose of clearly illustrating the present disclosure, and are not intended to limit the scope of the present disclosure. For those skilled in the art, other changes or modifications may be made based on the above disclosure, and these changes or modifications are still within the scope of the present disclosure.

Claims

1. A bionic super-hydrophobic sterilization film for the surface of home paving materials, characterized in that: Apply on the super-hydrophobic modified layer with concave micro-nano structure; in terms of mass percentage, it includes the following raw materials: Palygorskite nanofiber: 5%-8%; Silica nanoparticles: 10%-16%; Silane-polyurethane resin: 30%-45%; Tannic acid: 25%-35%; Titanium dioxide nanoparticles: 15%; The preparation method comprises the following steps: Taking half of the mass of tannic acid and adding it into water to fully dissolve it to form a solution, placing palygorskite nanofibers in the solution, adding silicon dioxide nanoparticles and stirring evenly, so that the silicon dioxide nanoparticles are in-situ grown on the surface of the palygorskite nanofibers to form a first composite solution; adding silane-polyurethane resin to the first composite solution and stirring evenly, so that the silane-polyurethane resin is grafted to the first composite solution containing silica nanoparticles / palyogorite nanofibers to form a second composite solution; The other half of the mass of tannic acid is dissolved in water, titanium dioxide nanoparticles are added and stirred evenly to form a third composite solution; the third composite solution is then added dropwise to the second composite solution, and stirring is performed during the adding process to obtain a finished composite solution.

2. A bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 1, characterized in that: The palygorskite nanofiber: 5%; Silica nanoparticles: 10%; Silane-polyurethane resin: 45%; Tannic acid: 25%; Titanium dioxide nanoparticles: 15%.

3. A bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 1, characterized in that: The palygorskite nanofiber: 8%; Silica nanoparticles: 16%; Silane-polyurethane resin: 30%; Tannic acid: 31%; Titanium dioxide nanoparticles: 15%.

4. A bionic super-hydrophobic sterilization film for the surface of home paving materials according to any one of claims 1 to 3, characterized in that: The particle size of the titanium dioxide nanoparticles is 5 nanometers.

5. A bionic super-hydrophobic sterilization film for the surface of home paving materials according to any one of claims 1 to 3, characterized in that: The grafting process comprises the steps of: S1. Select appropriate silane-polyurethane resin: the silane part should react with the hydroxyl groups on the surface of silica nanoparticles, and the polyurethane part should interact with the functional groups on the surface of palygorskite nanofibers; S2. Surface treatment: In the tannic acid environment, more hydroxyl and carboxyl groups are exposed on the surface of palygorskite; S3, silane-polyurethane resin and silica / palyogorite nanofibers were all modified to achieve click grafting; the grafting reaction was carried out at room temperature for 40 minutes and then the temperature was raised to 65 degrees Celsius for 60 minutes.

6. A bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 5, characterized in that: The type of silane in the silane-polyurethane resin is one of chlorosilane, methoxysilane and aminosilane.

7. The bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 5, characterized in that: After the grafting is completed, characterization and performance testing steps are carried out, and infrared spectroscopy is used to characterize the structure and grafting degree of the grafted product.

8. A method for using the bionic super-hydrophobic sterilization film on the surface of home paving materials as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Pretreatment: The pretreatment step includes substrate cleaning: using ultrasonic cleaning to remove impurities such as pollutants, grease, oxides, etc. on the surface of the substrate; S2: Pre-baking: Baking the substrate to a certain temperature to remove moisture and adsorbed gases in preparation for deposition; the temperature of the substrate is adjusted according to its material; S3: vacuum reaction chamber preparation: placing the treated substrate into the vacuum reaction chamber, and vapor deposition is performed in a low pressure or vacuum environment to ensure that the reaction gas molecules can move freely and reach the substrate surface; S4: heating the vacuum reaction chamber to a corresponding temperature according to the difference in substrate material and the preparation process of the super-hydrophobic modified layer of the concave micro-nano structure; S5: atomizing the prepared solution into fine droplets, and in the deposition chamber, using plasma, electron beam bombardment or laser irradiation to excite the atomized molecules into an active state to increase their adhesion and reactivity; S6: Thin film growth: The atomized molecules undergo physical deposition, and the deposits adhere to the substrate surface to form a thin film; S7: After the process is completed, the atomized molecule delivery is stopped and the reaction chamber is slowly restored to normal pressure.

9. The method for preparing a bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 8, characterized in that: In step S6, the ceramic substrate is dried in a vacuum reaction chamber at 300 degrees Celsius for 20-60 seconds and then cured at room temperature for 8 hours.

10. The method for preparing a bionic super-hydrophobic sterilization film for the surface of home paving materials according to claim 8, characterized in that: After the substrate is taken out, annealing and cooling are performed as post-processing steps to further improve the performance of the film.

Citation Information

Patent Citations

  • A durable, superhydrophobic, self-cleaning, and anti-slip ceramic tile and its preparation method.

    CN115611662B

  • Method for preparing hydrophobic film on surface of material

    CN101962769A

  • Aircraft coating and preparation method thereof, and method for forming aircraft coating

    CN103342953A

  • Method for improving mechanical stability of super-hydrophobic film on wood surface

    CN105563577A

  • Preparation method of superhydrophobic and super-lipophilic oil-water separation mesh membrane based on tannic acid modification

    CN109675445A